Ensuring the Principle of Independence of the Court in Adjudication under Vietnamese Criminal Procedure Law: A Mechanism to Ensure the Right to a Fair Trial - Hoang, Nguyen Anh (VNU Journal of Science: Legal Studies, 2023)
Building an independent judiciary is the goal of all nations today. The independence principle of the Court has been acknowledged in the first Constitution of Vietnam and has been continuously improved in all successive constitutions. The article focuses on discussing: (i) Primary issues of the independence principle of the Court in adjudication; (ii) Legal provisions on ensuring the independence of the Court in adjudication in accordance with national and international law; (iii) Practical issues of ensuring the independence of the Court in adjudication in Vietnam. Finally, the author makes several recommendations to ensure the independence of the Court in adjudication according to the Vietnamese Criminal Procedure Law.